The Influence Of Technological Advances, Management Knowledge, And User Participation In The Development Of Accounting Information Systems - Febriansyah, Erwin; Martya, Chendy; Azwani, Arina; Suyudi, Imam (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The development of Accounting Information Systems (AIS) has become a major focus in responding to the increasingly complex dynamics of modern business. This study aims to investigate the factors that influence the success of AIS development in the current industrial context. The research method used is a survey with a questionnaire distributed to managers and accounting professionals in various companies. Data analysis was carried out using multiple regression to evaluate the relationship between independent variables (technological progress, management knowledge, and user participation) with the dependent variable (success of AIS development).The results of the study indicate that technological progress adopted by the company, the level of management knowledge in integrating AIS with business strategy, and active user participation significantly contribute to the success of AIS development. Further regression analysis shows that there is a significant interaction between technological progress and user participation, indicating the importance of strategic integration between technology and human factors in AIS development.This study has significant implications for both practitioners and academics. For practitioners, these findings highlight the importance of managing organizational change and increasing user participation in maximizing the benefits of AIS technology investments. For academics, this study provides new insights in expanding management theory related to technology integration in accounting information systems.